Codebook Design for Parallel Dynamic Subarrays in Millimeter Wave Massive MIMO Systems - Qi Li; Fu-Chun Zheng; Ke Xu; Lianming Li (IEEE Open Journal of Vehicular Technology)
This paper investigates the codebook design for the novel parallel dynamic subarrays for millimeter-wave (mmWave) massive MIMO systems. To generate high-resolution patterns, we design a novel parallel dynamic subarray structure where each radio frequency (RF) chain is dynamically connected to a subarray consisting of an antenna subset from two parallel arrays. Given the high grating lobes, we further design a PS selection strategy and codeword to obtain a high-resolution pattern with low grating lobes. In particular, an exhaustive algorithm is first proposed to get the optimum subarray configuration strategy. The combined high-low resolution phase shifter (PS) architecture is then utilized to overcome the hardware limitation of constant amplitude. Finally, the cuckoo search algorithm is employed to search the phase distribution and obtain the final codeword. Simulation results demonstrate that the proposed scheme can generate high-resolution patterns with low grating lobes, thereby achieving improved system spectral efficiency (SE).